Professor Aleksander Opilski - Tadeusz PUSTELNY (Archives of Acoustics)
Professor Aleksander Opilski has passed away on 20 April 2012. Aleksander Opilski was born on 31 August 1931 in Zagórze in the then Śląskie Voivodship. He under-went his 1st level studies in the years 1950–1953 at the Faculty of Mathematics, Physics and Chemistry of the Jagiellonian University in Krakow. His 2nd level academic education was completed at the Adam Mickiewicz University in Poznań from which he graduated in 1958 as a Master of Science in Physics